METHODOLOGICAL APPROACHES TO THE TRANSFORMATION OF THE POTENTIAL-FORMING SPACE OF REGIONAL ECONOMIC SYSTEMS UNDER THE INFLUENCE OF INTELLECTUAL AND INNOVATIVE DETERMINANTS - KHANIN, SEMEN; DERHALIUK, MARTA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article investigates the methodological principles of transformation of the potential-forming space of regional economic systems under the influence of intellectual and innovative determinants, which is due to the need for further development of regions. It is substantiated that in the conditions of transformation of potential-forming space the development of regional economic systems is accompanied by multivariate socio-economic processes, which leads to the emergence of new challenges, threats and risks. Potential-forming space, the transformation of which affects the development of regional economic systems - is a complex systemic phenomenon, which consists of various resource, technological components. Based on a synergistic approach, a strategic-oriented model of the impact of the transformation of potential-forming space on the development of regional economic systems under the influence of intellectual and innovative determinants can be defined: as reproduction and maintenance of dynamic stability in relation to various factors, challenges, risks and threats. As well as as an activity that in the process of transformation of potential-forming space under the influence of intellectual and innovative determinants aims to take into account various factors and challenges, as well as external and internal environment that ensure stability of all components of regional economic systems. The system-forming properties of the transformation of the potential-forming space for the development of regional economic systems under the influence of intellectual and innovative determinants are highlighted. It is substantiated that the strategic-oriented model of transformation of potential-forming space for the development of regions under the influence of intellectual-innovative determinants outlines the details of such system-forming properties as: complex system, higher-level subsystem, adaptability to real transformations and dissipation. managerial, functional, production, social and other components.
Keywords: intellectual and innovative determinants; transformation; potential-forming space; regional economic system; synergistic approach